RANCANG BANGUN SISTEM MONITORING DAN OTOMATISASI PADA MODEL ZERO WASTE INTEGRATED FARMING SYSTEM (ZWIFS) BERBASIS INTERNET OF THINGS - Putra, Atha Darari; Zainuri, Akhmad; Abidin, Zainul (Jurnal Mahasiswa TEUB, 2024)
With the projection of the world population reaching 9.6 billion by 2050, the challenge of increasing foodproductionbecomes crucial. The lack of agricultural production growth can pose a threat of food crisis with wide-rangingimpactsoneconomic and social stability. The Indonesian government has responded by enacting Food Law Draft No. 18 of 2012, withthree main paradigms: Food Sovereignty, Food Self-Sufficiency, and Food Security. However, other challenges arise, suchas workforce regeneration in agriculture and reduction of agricultural land. Zero Waste Integrated FarmingSystem(ZWIFS), which integrates agriculture, fisheries, and livestock farming, offers a solution that can address all of thesechallenges. This system focuses on the harmony between natural resources, human resources, and the environment, withazero waste system approach. In the ZWIFS, elements such as aquaponic vegetable plants, chicken coops, maggotcultivation, and fish ponds interact synergistically. However, the management and maintenance of these various elementsrequire efficient monitoring and automation systems. This research aims to design and develop monitoring andautomationsystems in ZWIFS. This system includes real-time monitoring of air temperature, air humidity, water temperature, waterlevel, water pH, and water TDS. In addition, the automation system includes scheduled feeding, pumpandaeratorregulation, and automatic water sampling. The integration of this technology is expected to create an efficient, sustainable,and waste-free ZWIFS, providing positive impacts both economically and environmentally. Keyword: farming, Internet of Things, zero waste